The landscape and level of alcohol policy enforcement in Tanzania. - Kim Madundo; Aliza Hudda; Maaike L Seekles; Blandina Mmbaga; Angela Obasi (PLOS Global Public Health)
Harmful use of alcohol causes more deaths in Sub-Saharan Africa than in any other region. In Tanzania, where alcohol use disorders rates are twice the overall African average, harmful alcohol consumption is a public health concern. Given the lack of a contemporary overview of the alcohol policy landscape, we conducted a mixed-methods review of key alcohol-related policies, implementers, and initiatives in Tanzania. We conducted a desk-based review of policy-related documents, and in-depth interviews with eight key informants guided by the 10-composite-indicator framework of a tool for measuring alcohol policy implementation developed by World Health Organization. Representatives were from health-service delivery, community-based organizations, governmental organizations, research, and policymakers whose work is related to alcohol in Tanzania. Data was collected in June and October 2022, and finalized in March 2023. Findings were analyzed using Microsoft Word v2021. Themes were identified, collected, combined, and tabulated. Differences were then resolved by first and second authors. Our findings revealed no single comprehensive national alcohol policy. Pending finalization of a draft policy, various documents and actors govern alcohol production, distribution, licensing, and consumption. Little intersectoral linkage between entities contributes to poor enforcement of these regulations. Regulation is stronger in urban areas, and restrictions more effective on industrial alcohol. However, the majority of consumed alcohol in Tanzania is informally-produced, especially in rural settings. Socio-cultural context plays a key role in alcohol production and consumption, contributing to early-age exposure to alcohol. Alcohol is a growing source of revenue for the Tanzanian government and, therefore, imposing further restrictions is a low priority. There are important policy gaps in various sectors pertaining to alcohol regulation. Our results strongly suggest the need for a comprehensive approach to developing an overarching alcohol policy, with involvement of key stakeholders, stronger enforcement, and increased awareness, resources, and collaborations.